Influencing factors of home hospice care needs of family caregivers of the older adult with chronic diseases at the end of life in China: a cross-sectional study - Wang, Lei; Li, Yaru; Zhao, Rui; Li, Jiangxu; Gong, Xiangru; Li, Hongyu (Frontiers in Public Health, 2024)
With increased life expectancy in the Chinese population coupled with chronic disease the care needs of people at the end of life are attracting much attention. Home hospice care can help the dying elderly achieve comfort and maintain their dignity at home. However, dying at home means great responsibility and challenge for family caregivers, and there are many unmet needs. The study aimed to investigate the home hospice care needs of family caregivers of elderly people with chronic diseases at the end of life in China, and to analyze the influencing factors of home hospice care needs of caregivers.In this cross-sectional study, from May to September 2023, 4 community health service centers were selected by stratified sampling from 7 administrative districts in Jinzhou City, Liaoning Province, where home hospice care was piloted. Then 224 family caregivers were selected from the communities of 4 community service centers by simple random sampling method. A general information questionnaire and the home hospice care needs questionnaire developed by our research group were used to investigate. Univariate analysis was used to compare the differences in the scores of different characteristics, and the factors with significant differences were selected for multivariate linear regression analysis to determine the final influencing factors.The total score of hospice care needs of family caregivers was 121.61±15.24, among which the end-of-life knowledge need dimension score was 24.04±2.71, the highest score index was 80.13%, while the symptom control need score was 15.58±3.39, the lowest score index was 62.32%.In addition, Caregivers with caregiving experience, dying elderly with longer disease duration, and dying elderly with higher levels of education were the factors influencing the total need for home hospice care among family caregivers, with a variance explained of 22.7%.The needs of family caregivers of the terminally ill elderly are high, and healthcare professionals should implement services to meet their multidimensional needs and improve the quality of care according to the factors affecting their needs.